The role of contexts and polysemy in the historical development of new contrastive connectives - Ferrari, Luísa [UNESP] (Faculdade de Letras da UFMG, 2020)
This paper aims to investigate, in a longitudinal perspective, the historical development of contrastive constructions with agora (Portuguese) and of contrastive constructions with now (English) that express semantic opposition. In the light of the paths of change undergone by these constructions and of a theoretical framework that assigns to pragmatics the role of the chief driving force in change (TRAUGOTT; DASHER, 2002), the paper searches for evidence of the role of contexts and of polysemy in the development of new contrastive connectives. For this purpose, the research develops a diachronic study of contexts that provide conditions to the changes undergone by agora and by now, which are originally temporal adverbs. The results show, in accordance with Traugott (2012), that, if the development of new connectives involves grammaticalization, and not only meaning change, contexts that ally motivations for semantic-pragmatic reinterpretation and motivations for categorial reanalysis play a key role. Moreover, the diachronic analysis shows a great amount of similarities between the path of change undergone by agora and the path undergone by now, pointing to the productivity, across languages, of the temporal source as a derivation channel for contrastive meanings.
O papel dos contextos e da polissemia na constituição histórica de novos juntores contrastivos
Keywords: Contexts; Contrast; Grammaticalization; Polysemy